Canadian Public Library Users are Unaware of Their Information Literacy Deficiencies as Related to Internet Use and Public Libraries are Challenged to Address These Needs - Preddie, Martha Ingrid (Evidence Based Library and Information Practice, 2009)
A Review of: Julien, Heidi and Cameron Hoffman. “Information Literacy Training in Canada’s Public Libraries.” Library Quarterly 78.1 (2008): 19-41. Objective – To examine the role of Canada’s public libraries in information literacy skills training, and to ascertain the perspectives of public library Internet users with regard to their experiences of information literacy. Design – Qualitative research using semi-structured interviews and observations. Setting – Five public libraries in Canada. Subjects – Twenty-eight public library staff members and twenty-five customers. Methods – This study constituted the second phase of a detailed examination of information literacy (IL) training in Canadian public libraries. Five public libraries located throughout Canada were selected for participation. These comprised a large central branch of a public library located in a town with a population of approximately two million, a main branch of a public library in an urban city of about one million people, a public library in a town with a population of about 75,000, a library in a town of 900 people and a public library located in the community center of a Canadian First Nations reserve that housed a population of less than 100 persons. After notifying customers via signage posted in the vicinity of computers and Internet access areas, the researchers observed each patron as they accessed the Internet via library computers. Observations focused on the general physical environment of the Internet access stations, customer activities and use of the Internet, as well as the nature and degree of customer interactions with each other and with staff. Photographs were also taken and observations were recorded via field notes. The former were analyzed via qualitative content analysis while quantitative analysis was applied to the observations. Additionally, each observed participant was interviewed immediately following Internet use. Interview questions focused on a range of issues including the reasons why customers used the Internet in public libraries, customers’ perceptions about their level of information literacy and their feelings with regard to being information literate, the nature of their exposure to IL training, the benefits they derived from such training, and their desire for further training. Public service librarians and other staff were also interviewed in a similar manner. These questions sought to ascertain staff views on the role of the public library with regard to IL training; perceptions of the need for and expected outcomes of such training; as well as the current situation pertinent to the provision of IL skills training in their respective libraries in terms of staff competencies, resource allocation, and the forms of training and evaluation. Interviews were recorded and transcribed. Data were interpreted via qualitative content analysis through the use of NVivo software. Main Results – Men were more frequent users of public library computers than women, outnumbering them by a ratio ranging from 2:1 to 3.4:1. Customers appeared to be mostly under the age of 30 and of diverse ethnicities. The average income of interviewed customers was less than the Canadian average. The site observations revealed that customers were seen using the Internet mainly for the purposes of communication (e.g., e-mail, instant messaging, online dating services). Such use was observed 78 times in four of the libraries. Entertainment accounted for 43 observations in all five sites and comprised activities such as online games, music videos, and movie listings. Twenty-eight observations involved business/financial uses (e.g., online shopping, exploration of investment sites, online banking). The use of search engines (25 observations), news information (23), foreign language and forum websites (21), and word processing were less frequently observed. Notably, there were only 20 observed library-specific uses (e.g., searching online catalogues, online database and library websites). Customers reported that they used the Internet mainly for general web searching and for e-mail. It was also observed that in general the physical environment was not conducive to computer use due to uncomfortable or absent seating and a lack of privacy. Additionally, only two sites had areas specifically designated for IL instruction. Of the 25 respondents, 19 reported at least five years experience with the Internet, 9 of whom cited experience of 10 years or more. Self-reported confidence with the Internet was high: 16 individuals claimed to be very confident, 7 somewhat confident, and only 2 lacking in confidence. There was a weak positive correlation between years of use and individuals’ reported levels of confidence. Customers reported interest in improving computer literacy (e.g., keyboarding ability) and IL skills (ability to use more sources of information). Some expressed a desire “to improve certain personal attitudes” (30), such as patience when conducting Internet searches. When presented with the Association of College and Research Libraries’ definition of IL, 13 (52%) of those interviewed claimed to be information literate, 8 were ambivalent, and 4 admitted to being information illiterate. Those who professed to be information literate had no particular feeling about this state of being, however 10 interviewees admitted feeling positive about being able to use the Internet to retrieve information. Most of those interviewed (15) disagreed that a paucity of IL skills is a deterrent to “accessing online information efficiently and effectively” (30). Eleven reported development of information skills through self teaching, while 8 cited secondary schools or tertiary educational institutions. However, such training was more in terms of computer technology education than IL. Eleven of the participants expressed a desire for additional IL training, 5 of whom indicated a preference for the public library to supply such training. Customers identified face-to-face, rather than online, as the ideal training format. Four interviewees identified time as the main barrier to Internet use and online access. As regards library staff, 22 (78.6%) of those interviewed posited IL training as an important role for public libraries. Many stated that customers had been asking for formal IL sessions with interest in training related to use of the catalogue, databases, and productivity software, as well as searching the web. Two roles were identified in the context of the public librarian as a provider of IL: “library staff as teachers/agents of empowerment and library staff as ‘public parents’” (32). The former was defined as supporting independent, lifelong learning through the provision of IL skills, and the latter encompassing assistance, guidance, problem solving, and filtering of unsuitable content. Staff identified challenges to IL training as societal challenges (e.g., need for customers to be able to evaluate information provided by the media, the public library’s role in reducing the digital divide), institutional (e.g., marketing of IL programs, staff constraints, lack of budget for IL training), infrastructural (e.g., limited space, poor Internet access in library buildings) and pedagogical challenges, such as differing views pertinent to the philosophy of IL, as well as the low levels of IL training to which Canadian students at all levels had been previously exposed. Despite these challenges library staff acknowledged positive outcomes resulting from IL training in terms of customers achieving a higher level of computer literacy, becoming more skillful at searching, and being able to use a variety of information sources. Affective benefits were also apparent such as increased independence and willingness to learn. Library staff also identified life expanding outcomes, such as the use of IL skills to procure employment. In contrast to customer self-perception, library staff expressed that customers’ IL skills were low, and that this resulted in their avoidance of “higher-level online research” and the inability to “determine appropriate information sources” (36). Several librarians highlighted customers’ incapacity to perform simple activities such as opening an email account. Library staff also alluded to customer’s reluctance to ask them for help. Libraries in the study offered a wide range of training. All provided informal, personalized training as needed. Formal IL sessions on searching the catalogue, online searching, and basic computer skills were conducted by the three bigger libraries. A mix of librarians and paraprofessional staff provided the training in these libraries. However, due to a lack of professional staff, the two smaller libraries offered periodic workshops facilitated by regional librarians. All the libraries lacked a defined training budget. Nonetheless, the largest urban library was well-positioned to offer IL training as it had a training coordinator, a training of trainers program, as well as technologically-equipped training spaces. The other libraries in this study provided no training of trainers programs and varied in terms of the adequacy of spaces allocated for the purpose of training. The libraries also varied in terms of the importance placed on the evaluation of IL training. At the largest library evaluation forms were used to improve training initiatives, while at the small town library “evaluations were done anecdotally” (38). Conclusion – While Internet access is available and utilized by a wide cross section of the population, IL skills are being developed informally and not through formal training offered by public libraries. Canadian public libraries need to work to improve information literacy skills by offering and promoting formal IL training programs.